Simple Statistical Testing on Existing Data of Core 39 KL SO189/2 to Reveal its Correlation Towards Sea Surface Temperature Variation - Taufan Wiguna; Khoiril Anwar Maryunani; Mirzam Abdurrachman; Yusuf Surachman Djajadihardja (Marine Geological Institute of Indonesia, 2020)
Several paleotemperature proxies using marine core sediment data have been developed and well-proven, but they need excellent laboratory handling and destructive tools. Spectrophotometer and Multi-Sensor Core Logger (MSCL) is considered rapid and non-destructive tools compared to other climate proxies. This paper enhances the correlation between existing data of spectrophotometer, MSCL, and sea surface temperature (SST) of the sediment core 39 KL from SO189/2 through a statistical test. The dataset is processed using interpolation, Pearson correlation, and K-means clustering. Pearson correlation reveals a strong correlation between spectrophotometer, MSCL, and SST. K-means clustering points out that SST is shifting from relatively colder to warmer. This study also tries to understand the source of four tephra and one terrigenous layer. It can be concluded that the spectrophotometer and MSCL have a positive correlation to SST variation. Keywords: statistical approach, existing data of SO189/2, spectrophotometer, Multi-Sensor Core Logger, sea surface temperatureBeberapa proksi paleotemperature menggunakan sedimen inti laut telah dikambangkan dan terbukti baik, namun membutuhkan penanganan laboratorium yang bagus dan bersifat destruktif. Spektrofotometer dan Multi Sensor Core Logger (MSCL) relatif lebih cepat dan tidak destruktif. Makalah ini membahas hubungan antara spektrofotometer, MSCL, dan temperature muka laut (SST) berdasarkan data sedimen inti 39 KL dari SO189/2 melalui pendekatan statistik. Data diolah menggunakan metode interpolasi, korelasi Pearson, dan kluster K-means. Korelasi Pearson menunjukkan korelasi kuat antara spektrofotometer, MSCL, dan SST. Kluster K-means menunjukkan pergeseran SST dari kondisi yang lebih dingin ke lebih hangat hubungan Stufi ini juga mencoba untuk memahami sumber 4 lapisan tefra dan 1 lapisan mineral terrigenous. Melalui studi ini, dapat disimpulkan bahwa spektrofotometer dan MSCL mempunyai korelasi positif terhadap variasi SST.Kata Kunci: Pendekatan statistik, Data existing SO189/2, spektrofotometer, Multi Sensor Core Logger, Suhu Permukaan Laut